UNDERSTANDING THE CONCEPT, EVOLUTION AND FUTURE SCOPE OF INTEGRATED MARKETING COMMUNICATIONS (IMC) - Das, Debasis (International Journal of Psychosocial Rehabilitation, 2021)
The importance of brand communication in today’s world cannot be overstated, as it has become a must for business sustainability. With the passing years , marketing communication has grown continuously, and the sky is still the goal. The necessity for Integrated Marketing Communications (IMC) grew as a result of the desire to fine-tune a central message across many communication platforms such as advertising, sales promotion, the Internet and interactive media, media affairs, and direct selling. The purpose of this study is to conduct a literature review and to have a better understanding of the concept, development, and future potential of Integrated Marketing Communications. Integrated Marketing Communications can be more specific, tailored, and digitized with the use of technology-based gear and software. It can quickly contact target audiences and transmit a central message that is tailored to each and every one of them. Practiced marketers and agencies are increasingly successfully integrating stand-alone traditional communication. Recent technological advances have made it easier to integrate communication across tools and platforms, allowing for easier performance tracking, ready-to-click statistics, and cheap customer conversion costs. The integration of Marketing Communication (MarCom) and its effects are examined here with the goal of creating a roadmap for future Integrated Marketing Communications.